(untitled) (The Pakistan Development Review, 1994)
The main concern of this volume is to explore various aspects of the research methodology relating to population dynamics. The authors belong to different disciplines, and in the nineteen contributions here which are categorised under five major themes, they examine various avenues relating to the assessment of population issues from their own perspectives. The first two papers ("Implicit Theoretical Assumptions in Research Designs" by Hubert M. Blalock Jr. and "Conceptual Models in Population Studies" by K. Mahadevan) emphasise the need for greater sensitisation of the researcher to a broad range of implicit assumptions in the research design for data analysis, and to the utilisation of appropriate conceptual frameworks for modern empirical research. Blalock rightly points out the general tendency of researchers to develop what he terms "intellectual blinders" to overlook the shortcomings of the design they adopt, and the tendency to stress the weaknesses of the unfavoured design strategies. He is also concerned about the generalisability issues when convenience of choice in the subject’s location in social psychology is excused on the grounds that it is also done by most others. He observes that the exposure of graduate students to the methodological literature is brief and, in many cases, it is only a "nuts and bolts treatment" of measurement issues with "a rather heavy emphasis on whatever technique happens to be fashionable at the time, or at their own universities, rather than a more thorough grounding on the nature of the theoretical assumptions that undergird the particular technique. As a result, they know how to use and churn out research papers that enable them to display their expertise. But they are not being trained to examine the approach in question from the standpoint of gaining a deeper understanding of the theoretical rationale that underlies it". (p. 34).